ANALISIS KORELASI KOEFISIEN KONTINGENSI PADA KONDISI FAKTOR SUFFICIENT TBC DENGAN KEJADIAN PENULARAN TBC PADA ANGGOTA KELUARGA PENDERITA TBC DI WILAYAH KERJA PUSKESMAS TALUN KENAS - Novrika Silalahi; Reni Aprinawaty Sirait; Agus Romendra (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2021)
Tuberculosis case have high rate, based on WHO (World Health Organization) have much 10,4 million people have TBC in the world. In southeast Asia 842.000 case with 107.000 mortality case. Tuberculosis is infectious diseases caused by Microbacterium Tuberculosis germ, if someone immune exposure Microbacterium Tuberculosis is low, low nutritional, bad environment that support Microbacterium Tuberculosis breeding, social economic condition is low and bad behavior (Suharyo,2016) then transmission potential TBC be big. The aim this research for know related sufficient condition factor TBC in sufferer TBC family with transmission incidental TBC in Talun Kenas Publich Health Center working area.This research use crossectional with descriptive desain. Research population is all of sufferer TBC family recorded from January to December 2019 in Talun Kenas Public Health Center. The sample is 41 sufferer TBC family. Research instrument is with use quisioner, checklist form, and observasion form. Chisquare test result are : (1) Knowledge (P=0,043, OR=5,7); (2) Attitude (p=0,040, OR=6,25); (3) Action (p=0,045, OR= 4,4); Nutritional (p=0,025, OR=6,6); Physical condition of the house (p=0,021, OR= 8,2).ConclusionL1) There is a significant relationship of knowledge with the incidence of TBC transmission.(2).There is significant relationship of attitude with the incidence of TBC transmission.(3) There is significant relationship of action with the incidence of TBC transmission.(4). There is Significant relationship of Nutritional with the incidence of TBCtransmission.(5). There is significant relationship of physical condition of the house with incidence of TBC transmission.